2018
DOI: 10.1513/annalsats.201708-663oc
|View full text |Cite
|
Sign up to set email alerts
|

Transitions to Home Mechanical Ventilation. The Experiences of Canadian Ventilator-assisted Adults and Their Family Caregivers

Abstract: Transition to HMV is a complex and demanding process. Extended HMV training and support may be helpful in mediating adjustment challenges thus reducing stress, caregiver burden and improving health related quality of life for VAIs and family caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(65 citation statements)
references
References 31 publications
1
63
0
1
Order By: Relevance
“…review after HMV commencement, there was no difference in the need for emergent care or hospital admission. Reasons for this might reflect ongoing disease progression or may relate to the limited availability of community healthcare workers for ventilator-assisted individuals [41].…”
Section: Discussionmentioning
confidence: 99%
“…review after HMV commencement, there was no difference in the need for emergent care or hospital admission. Reasons for this might reflect ongoing disease progression or may relate to the limited availability of community healthcare workers for ventilator-assisted individuals [41].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research investigating transitions to home mechanical ventilation similarly reported patient preference for personalized and ongoing support from respiratory health professionals. 27 Proactive RT educator follow-up detailing an individualized MI-E prescription, user technique, device cleaning, and methods for obtaining replacement parts is supported by growing evidence suggesting that patients with chronic conditions do better with selfmanagement through regular follow-up 28 comprising educational, supportive, or behavioral interventions. 20 Strengths of this study are the inclusion of new and established MI-E users and family caregivers representing variations in age, primary diagnosis, and treatment independence.…”
Section: Discussionmentioning
confidence: 99%
“…15 Although not specific to airway clearance, data from a qualitative interview study of 33 individuals receiving home ventilation and their family caregivers also identified a need for home outreach and increased training of community health care providers as potential facilitators to transition to home mechanical ventilation. 21…”
Section: Discussionmentioning
confidence: 99%